An Integrated Care Initiative to Improve Patient Outcome in Schizophrenia - Mayer-Amberg, Norbert; Woltmann, Rainer; Walther, Stefanie (Frontiers in Psychiatry, 2016)
The optimal treatment of schizophrenia patients requires integration of medical and psychosocial inputs. In Germany, various healthcare service providers and institutions are involved in the treatment process. Early and continuous treatment is important but often not possible because of the fragmented medical care system in Germany. The current work is a quality monitoring report of a novel care setting, called Integrated Care Initiative Schizophrenia. It has implemented a networked care concept in the German federal state of Lower Saxony that integrates various stakeholders of the health care system. In this initiative, office-based psychiatrists, specialised nursing staff, psychologists, social workers, hospitals, psychiatric institutional outpatient’s departments and other community-based mental health services work together in an interdisciplinary approach. Much emphasis is placed on psychoeducation. Additional efforts cover socio-therapy, visiting care, and family support. During the period from October 2010 (start of the initiative) to December 2012, first experiences and results of quality indicators were collected of 713 registered patients and summarised in a quality monitoring report. In addition, standardised patient interviews were conducted, and duration of hospital days was recorded in 2013. By the end of 2012, patients had been enrolled for an average of 18.7 months. The overall patient satisfaction measured in a patient survey in June 2013 was high and the duration of hospital days measured in a pre-post analysis in July 2013 was reduced by 44%. Two years earlier than planned, the insurance fund will continue the successfully implemented integrated care initiative and adopt it in the regular care setting. This initiative can serve as a learning case for how to set up and measure integrated care systems that may improve outcomes for patients suffering from schizophrenia.